Cantos e encantos: os rumos da história da mídia sonora para crianças no Brasil - Cappi, Juliano (2007)
The research aims to carry out a historiographic rising of the sound media works for children in Brazil. The central objective consists in offering a general and temporalized idea of the workmanships that have been considered significant, and propose criterias for approaching the object. The criteria to chose the workmanships was the following ones: a) the works that have been launched to the market; b) the relevance of the workmanship for the public and the market; c) the relevance of the workmanship for the guidelin developed specifically in this essay; d) the choice of exclusively sonorous supports as LPs and CDs, what cuts off an important source of infantile sonorous works from the focus of the essay: the radio. The problem was raised from the revelation that the object does not have been researched at all. This survey is in the truth a study of historical reconstruction of the Brazilian culture. To carry through the analyses along the essay the concept of enchantment developed by the psychoanalyst Boris Cyrulnik was fundamental. The history of the media and its influence in the sonorous production for children are its line master. The enchantment offers a perspective to analyze on one hand the search for technological innovations that makes the media apparatus more attractive, and on the other hand the influence in the development of contents for the infantile programs that became more and more apealing. The studies on culture of Edgar Morin and Ivan Bystrina, the studies on image of Vilem Flusser and the iconophagy theory of Norval Baitello Junior have been also used. The analysis corpus structure is based in the relation between the media history and the sonorous media works for children, or either, from an approach of these two historys. During the text they are worked jointly through a net of linked events that helps us to better understand the movements of the infantile records history. From the decade of 1980 the execution of sonorous infantile works had been intensevely focused on the television programs. However, for our surprise in the same decade new artists appear to start exploring the development of different infantile sonorous works opening a broad range ways for this type of production